Investigating the factors affecting participation in natural resources development cooperatives: The case study of Ardabil Province. (25th August 2022) - Hamidi, Ali; Mehrabi, Aliakbar; Javadi, Seyed Akbar; Imani, Aliakbar
Abstract: Natural resources development cooperatives (NRDCs) are leading enterprises that develop sustainable community‐based solutions. Basically, such cooperatives attempt to engage beneficiaries in environmental conservation through collective action. However, there exist remarkable shortcomings in administering these types of cooperatives. This paper aims to investigate beneficiaries' willingness to participate and invest in NRDCs based on three educational, economic, and social sections, each represented by their corresponding components, which represent the variables (sub‐factors) of each section. The current research was performed using a descriptive‐survey approach. Semi‐structured interviews were conducted with 63 cooperatives' board members located in Ardabil Province in Iran. Results discovered that three variables of information, participation acceptance rate and top‐down planning from educational factors alongside those of conservation effectiveness and projected outlook from the economic factor significantly affect participation levels in NRDCs. Similarly, the lack of rangeland ownership, cooperatives' limited problem‐solving capabilities, and concerns about environmental conservation of formerly demolished lands, all components of the social section investigated in this study, highly influenced beneficiaries' participation in cooperatives. Correlation coefficient analysis between the efficient factors showed that education levels have no significant relationship with the two remaining factors; however, the economic and social factors positively and significantly ( p < 0.01) relate to beneficiaries' participation level. Nonparametric correlation analysis determined that variables from the economic factor analysis, such as the financial capital size, awareness levels, indigenous culture, people's experiences interacting with the administrative bodies of NRDCs, the state‐run economy, and the lack of support for beneficiaries by cooperatives from the social factor analysis each have independent and distinct relationships that affect participation in cooperatives. However, from the educational factor analysis, all variables were influenced reciprocally and were of inferior importance to participation in NRDCs.